Pengaruh Perceraian terhadap Perkembangan Mentalitas Anak - Nurwada, Yesika; Anwar, Reski; Hikmah, Karimatul; Fatmawati, Fatmawati (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2024)
In a family, harmonious relationships between parents and between parents and children will have a positive impact on the child's growth and development process. However, in reality, the wheel of life always turns faster for some families, disputes, misery, harmony and suffering seem to come and go, causing divorce which then has a negative impact on their children. This research aims to analyze the impact of divorce on children's mental health and growth and development. In this research, the author will explain the impact of divorce on children's mental health, because generally when parents divorce, the main impact of the divorce is the child. Lack of parental attention and love for children will decrease or even disappear after they divorce, this will cause anxiety, restlessness, confusion and sadness for a child, which will then disrupt mental development and the process of growth and development, especially for children who are at the age of during adolescence, there is a high possibility that they will experience emotional disturbances which will ultimately lead them to juvenile delinquency which will damage their future. Keywords: Family, Divorce, Child Mental Health